Global miRNA to miRNA Interactions: Impacts for miR-21. Issue 1 (January 2021) - Hill, Meredith; Tran, Nham
Abstract : miRNAs inherently alter the cellular environment by regulating target genes. miRNAs may also regulate other miRNAs, with far-reaching influence on miRNA and mRNA expression. We explore this realm of small RNA regulation with a focus on the role of the oncogenic miR-21 and its impact on other miRNA species.